2010
DOI: 10.1111/j.1552-6569.2009.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postoperative Status after Clipping Surgery in Patients with Cerebral Aneurysm on 3-Dimensional-CT Angiography with Elimination of Clips

Abstract: 3D-CTA with elimination of bone and clips can improve the accuracy of detection of remnant necks after clipping surgery for cerebral aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Tomura, [13] 2009 Japan 39 43 32 and 64 C 13 P = Prospective; R = Retrospective; C = Consecutive; NR = Not reported, QUADAS score = The quality assessment of diagnostic accuracy studies score …”
Section: Quadas Scorementioning
confidence: 99%
See 2 more Smart Citations
“…Tomura, [13] 2009 Japan 39 43 32 and 64 C 13 P = Prospective; R = Retrospective; C = Consecutive; NR = Not reported, QUADAS score = The quality assessment of diagnostic accuracy studies score …”
Section: Quadas Scorementioning
confidence: 99%
“…All the time, both computed tomographic angiography (CTA) and digital subtraction angiography (DSA) are deemed as valuable tools to detect cerebral aneurysms, whereas the residual or recurrent aneurysms after clipping is mainly evaluated by the use of DSA. [14] As DSA is invasive as well as time and money consuming, an increasing number of articles have reported CTA as a noninvasive screening method for the postoperative assessment of clipped aneurysms, [4][5][6][7][8][9][10][11][12][13] and with recent technological developments, some authors believe that CTA can even replace DSA for routine postoperative assessment of clipped aneurysms. [5,15] test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual aneurysm rate varied from 5.7% to 18% in previous articles (8). Previously it seemed that small neck remnants were not important, but it has been shown that these small neck remnants grow again and become dangerous in long term (7).…”
Section: Introductionmentioning
confidence: 96%
“…Incomplete aneurysm clipping leads to re-bleeding with fatal complications (6,7). Residual aneurysm rate varied from 5.7% to 18% in previous articles (8).…”
Section: Introductionmentioning
confidence: 99%